Quinone-based fluorophores for imaging biological processes. (3rd November 2017) - Dias, Gleiston G.; King, Aaron; de Moliner, Fabio; Vendrell, Marc; da Silva Júnior, Eufrânio N.
Abstract : This tutorial review covers recent advances in the design, synthesis and application of quinone-based fluorescent agents for visualizing specific processes in multiple biological systems, from cells to tissues and complex organisms in vivo . Abstract : Quinones are privileged chemical structures playing crucial roles as redox and alkylating agents in a wide range of processes in cells. The broad functional array of quinones has prompted the development of new chemical approaches, including C–H bond activation and asymmetric reactions, to generate probes for examining their activity by means of fluorescence imaging. This tutorial review covers recent advances in the design, synthesis and applications of quinone-based fluorescent agents for visualizing specific processes in multiple biological systems, from cells to tissues and complex organisms in vivo .